PENGARUH EKSTRAK DAUN JERUJU (Acanthus ilicifolius) TERHADAP PENINGKATAN KADAR HDL DARAH PADA TIKUS PUTIH (Rattus norvegicus) JANTAN GALUR WISTAR YANG DIINDUKSI ALOKSAN - angling febriani (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2022)
Introduction: Among people with Diabetes Mellitus, type 2 is the most common sufferer among others. Jeruju leaves which contain flavonoids are considered to have a beneficial effect against Diabetes Mellitus through the ability to reduce glucose and increase glucose tolerance. Objectives: This iresearch iaims ito idetermine ithe ieffect iof iJeruju i(Acanthus iilicifolius) ileaf iextract on ielevated ilevels iof iHDL iblood iof iwhite irats i(Rattus inorvegicus) imale iwistar-induced ialloxan Methods: The study used a laboratory experimental method with a post test only control group design, using 24 male white rats of the Wistar strain, which were divided into 3 groups: 1) a group of rats fed standard diet; 2) groups of rats fed standard feed and alloxan induction; 3) a group of rats fed standard feed and alloxan induction and given jeruju (Acanthus ilicifolius) leaf extract. Results: The study stated that there was no significant difference (p = 0.120) in HDL levels in the experimental group fed the standard diet and the experimental group fed the standard feed and alloxan induction. Conclusion: There was a significant difference (p=0.005) in HDL levels between groups of experimental animals given alloxan induction and experimental animals given alloxan induction and jeruju leaf extract (Acanthus ilicifolius). HDL levels of male white rats of wistar strain that were given standard feed, alloxan induction, and jeruju leaf extract increased. Keywords: aloksan, high-density lipoprotein, Acanthus ilicifolius